Investigations on the C-Rate and Temperature Dependence of Manganese Dissolution/Deposition in LiMn2O4/Li4Ti5O12 Lithium Ion Batteries. Issue 6 (1st January 2016) - Börner, M.; Klamor, S.; Hoffmann, B.; Schroeder, M.; Nowak, S.; Würsig, A.; Winter, M.; Schappacher, F. M.
Abstract : LiMn2 O4 / Li4 Ti5 O12 based lithium ion batteries were aged at different cycling conditions to investigate the deposition of dissolved manganese species on the surface of the anode. Surface-sensitive analysis methods were applied to determine the nature of the manganese containing deposits concerning their structure, composition and morphology. The results reveal that the dissolved species form discrete particles with a nano-crystalline structure that mainly consists of manganese oxides, fluoride and carbonate. Additional analytical methods and mapping experiments were used to investigate the overall amount of the deposited manganese species and its dependence on the cycling conditions. The temperature has only minor influence on the amount of manganese deposition on the anode in the range of 23°C to 45°C. However, the investigations show a direct influence of the C-rate on the dissolution and deposition of manganese species. At low C-rates the dissolved species deposit in the form of a limited number of nuclei that grow separately from each other. Higher C-rates of up to 4C lead to a change in the shape and the amount of deposited manganese species.